TANGGUNG GUGAT KEPERDATAAN TERHADAP PENGGUNAAN MEREK MS GLOW SECARA ILEGAL - ARINI PUTRI; Aris Munandar (Private Law, 2023)
The widespread use of Marks without permission by piggybacking or piggybacking Brands that are well-known or have a high reputation. This action is called Passing Off, which is an action that instantly tries to take advantage by piggybacking by imitating the property of another party with a good reputation. This study uses normative research methods using 3 (three) approach methods: the statute approach, the case approach, and the conceptual approach. As for the research results related to the decision, the authors agree with the judge's decision, including the dispute was based on an unlawful act, in the end, resulting in material and immaterial losses for the plaintiff naturally carries out the compensation and termination of actions related to the use of the mark without. The decision of the panel of judges to grant exclusive rights to the use of the "PS GLOW" trademark is correct. MS GLOW registered the brand earlier than PS GLOW, on September 20, 2016, but with the name MS GLOW FOR BEAUTIFUL SKINCARE, not just MS GLOW.